Pelaksanaan Sanksi Denda E-Tilang Bagi Pelanggar Lalu Lintas - Dessi Perdani Yuris Puspita Sari; Rani Hendriana (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2019)
One solution to enforce traffic violation is by using E-ticket (e-tilang) penalties for traffic violators. Conceptually, E-tilang is the settlement of electronic-based traffic violation cases through information system and technology, as stated in Article 1 number 2 of the Republic of Indonesia Supreme Court Regulation Number 12 of 2016 concerning how to resolve traffic violation cases. E-tilang is considered able to provide more practical and fast service compared to conventional ticket. The problem in this study is to identify how is the implementation and constraints of the e-tilang system fine sanctions in the settlement of traffic violations cases in Banyumas police station jurisdiction? This research is an empirical study using sociological juridical approach. The data is processed in a qualitative descriptive manner. The focus of this research is the implementation of e-tilang penalties for traffic offenders in Banyumas. The results of this study describe the application of e-tilang to facilitate the speed, convenience, and openness of the implementation of the ticketing process to replace in-place ticketing process.